Communicative Competence in Current Mathematics Teachers Formation in Chile [Competencia Comunicativa en la Formación Inicial Actual del Profesor de Matemática en Chile] - Vargas-Diaz, C; Apablaza-Apablaza, H (Centro de Informacion Tecnologica, 2019)
In this paper the current state in the development of communicative competence in mathematics teachers formation in Chile is discussed and analyzed. The online descriptions of the mathematic teachers formation programs for the universities that are part of the Rectors Council of Chilean Universities were obtained. A questionnaire was designed to explore the opinions of the directors of these programs about the formation in communicative competences. The results show that there are some common erroneous conceptions. For instance, that the communicative competence of mathematics teachers is still considered part of oral and written communication, that is to say: as a general ability instead of an ability specialized for teaching mathematics. It is concluded that in Chile it is still necessary to introduce the development of communicative competences in mathematics teaching during the initial formation of future teachers. © 2019 Centro de Informacion Tecnologica.